Pregunta
upstudy study bank question image url

Quadratic equations (common fada) Solve for \( x \) : a. \( x^{2}-11 x=0 \) b. \( 2 x^{2}=3 x \) c. \( 12 x^{2}=10 x \) d. \( 5 x(x-2)+3(x-2)=0 \) e \( (2 x-3)(x+2)-5(x+2)=0 \) f. \( 5(x-7)^{2}-(x-7)=0 \) i \( (x-3)^{2}=x(x-3) \)

Ask by Lynch Sherman. in South Africa
Feb 19,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions for each quadratic equation: a. \( x = 0 \) or \( x = 11 \) b. \( x = 0 \) or \( x = 1.5 \) c. \( x = 0 \) or \( x = 0.8333 \) d. \( x = -0.6 \) or \( x = 2 \) e. \( x = -2 \) or \( x = 4 \) f. \( x = 7 \) or \( x = 7.2 \) i. \( x = 3 \)

Solución

Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-11x=0\) - step1: Factor the expression: \(x\left(x-11\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-11=0\\&x=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=11\\&x=0\end{align}\) - step4: Rewrite: \(x_{1}=0,x_{2}=11\) Solve the equation \( (x-3)^{2}=x(x-3) \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left(x-3\right)^{2}=x\left(x-3\right)\) - step1: Multiply the terms: \(\left(x-3\right)^{2}=x^{2}-3x\) - step2: Expand the expression: \(x^{2}-6x+9=x^{2}-3x\) - step3: Cancel equal terms: \(-6x+9=-3x\) - step4: Move the variable to the left side: \(-6x+9+3x=0\) - step5: Add the terms: \(-3x+9=0\) - step6: Move the constant to the right side: \(-3x=0-9\) - step7: Remove 0: \(-3x=-9\) - step8: Change the signs: \(3x=9\) - step9: Divide both sides: \(\frac{3x}{3}=\frac{9}{3}\) - step10: Divide the numbers: \(x=3\) Solve the equation \( 12 x^{2}=10 x \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(12x^{2}=10x\) - step1: Move the expression to the left side: \(12x^{2}-10x=0\) - step2: Factor the expression: \(2x\left(6x-5\right)=0\) - step3: Separate into possible cases: \(\begin{align}&6x-5=0\\&2x=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=\frac{5}{6}\\&x=0\end{align}\) - step5: Rewrite: \(x_{1}=0,x_{2}=\frac{5}{6}\) Solve the equation \( 2 x^{2}=3 x \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}=3x\) - step1: Move the expression to the left side: \(2x^{2}-3x=0\) - step2: Factor the expression: \(x\left(2x-3\right)=0\) - step3: Separate into possible cases: \(\begin{align}&2x-3=0\\&x=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=\frac{3}{2}\\&x=0\end{align}\) - step5: Rewrite: \(x_{1}=0,x_{2}=\frac{3}{2}\) Solve the equation \( 5 x(x-2)+3(x-2)=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(5x\left(x-2\right)+3\left(x-2\right)=0\) - step1: Factor the expression: \(\left(x-2\right)\left(5x+3\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&5x+3=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-\frac{3}{5}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{3}{5},x_{2}=2\) Solve the equation \( (2 x-3)(x+2)-5(x+2)=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(\left(2x-3\right)\left(x+2\right)-5\left(x+2\right)=0\) - step1: Factor the expression: \(\left(x+2\right)\left(2x-3-5\right)=0\) - step2: Separate into possible cases: \(\begin{align}&2x-3-5=0\\&x+2=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=4\\&x=-2\end{align}\) - step4: Rewrite: \(x_{1}=-2,x_{2}=4\) Solve the equation \( 5(x-7)^{2}-(x-7)=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(5\left(x-7\right)^{2}-\left(x-7\right)=0\) - step1: Remove the parentheses: \(5\left(x-7\right)^{2}-x+7=0\) - step2: Expand the expression: \(5x^{2}-71x+252=0\) - step3: Factor the expression: \(\left(x-7\right)\left(5x-36\right)=0\) - step4: Separate into possible cases: \(\begin{align}&5x-36=0\\&x-7=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=\frac{36}{5}\\&x=7\end{align}\) - step6: Rewrite: \(x_{1}=7,x_{2}=\frac{36}{5}\) Here are the solutions for each of the quadratic equations: a. For the equation \( x^{2}-11 x=0 \): - Factoring gives \( x(x - 11) = 0 \). - Thus, the solutions are: \[ x_{1} = 0, \quad x_{2} = 11 \] b. For the equation \( 2 x^{2}=3 x \): - Rearranging gives \( 2x^{2} - 3x = 0 \). - Factoring gives \( x(2x - 3) = 0 \). - Thus, the solutions are: \[ x_{1} = 0, \quad x_{2} = \frac{3}{2} \quad \text{(or } 1.5\text{)} \] c. For the equation \( 12 x^{2}=10 x \): - Rearranging gives \( 12x^{2} - 10x = 0 \). - Factoring gives \( 2x(6x - 5) = 0 \). - Thus, the solutions are: \[ x_{1} = 0, \quad x_{2} = \frac{5}{6} \quad \text{(or } 0.8333\text{)} \] d. For the equation \( 5 x(x-2)+3(x-2)=0 \): - Factoring gives \( (x - 2)(5x + 3) = 0 \). - Thus, the solutions are: \[ x_{1} = -\frac{3}{5} \quad \text{(or } -0.6\text{)}, \quad x_{2} = 2 \] e. For the equation \( (2 x-3)(x+2)-5(x+2)=0 \): - Factoring gives \( (x + 2)(2x - 8) = 0 \). - Thus, the solutions are: \[ x_{1} = -2, \quad x_{2} = 4 \] f. For the equation \( 5(x-7)^{2}-(x-7)=0 \): - Factoring gives \( (x - 7)(5(x - 7) - 1) = 0 \). - Thus, the solutions are: \[ x_{1} = 7, \quad x_{2} = \frac{36}{5} \quad \text{(or } 7.2\text{)} \] i. For the equation \( (x-3)^{2}=x(x-3) \): - Rearranging gives \( (x - 3)(x - 3 - x) = 0 \). - Thus, the solution is: \[ x = 3 \] These are the solutions for each of the quadratic equations provided.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

For the equation \( x^{2}-11 x=0 \), factor out \( x \) to get \( x(x-11)=0 \), giving solutions \( x=0 \) or \( x=11 \). The second equation \( 2 x^{2}=3 x \) can be rearranged to \( 2 x^{2}-3 x=0 \) and factored as \( x(2x-3)=0 \), yielding \( x=0 \) or \( x=\frac{3}{2} \). Continuing, for \( 12 x^{2}=10 x \), we rearrange to \( 12 x^{2}-10 x=0 \), allowing us to factor \( 2 x(6x-5)=0 \), giving solutions \( x=0 \) or \( x=\frac{5}{6} \). Next, the expression \( 5 x(x-2)+3(x-2)=0 \) can be factored out as \( (x-2)(5x+3)=0 \), leading to \( x=2 \) or \( x=-\frac{3}{5} \). For \( (2 x-3)(x+2)-5(x+2)=0 \), we can simplify to \( (x+2)(2x-3-5)=0 \), or \( (x+2)(2x-8)=0 \) which gives us solutions \( x=-2 \) or \( x=4 \). The equation \( 5(x-7)^{2}-(x-7)=0 \) can be set as \( (x-7)(5(x-7)-1)=0 \) leading to \( x=7 \) or \( x=7-\frac{1}{5} \), yielding \( x=7 \) or \( x=\frac{34}{5} \). Finally, \( (x-3)^{2}=x(x-3) \) can be expanded and rearranged to \( (x-3)^{2}-x(x-3)=0 \), leading to \( (x-3)(x-3-x)=0 \), giving \( x=3 \) or \( x=0 \). All those solutions showcase the unique beauty of quadratic equations and reveal how they can embody unexpected twists and turns, much like a good plot in a novel! Quadratic equations have a long-standing history in mathematics, tracing back to ancient civilizations like the Babylonians and Greeks who were among the first to study them. The standard form \( ax^2 + bx + c = 0 \) emerged over centuries, culminating in the quadratic formula that we still use today to find solutions efficiently. In the modern world, quadratic equations find real-world applications in various fields such as physics to model projectile motion, finance to calculate profit margins, and engineering to design curves and structures. Understanding how to solve them can open up a world of possibilities in both academic and professional realms!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad